Pakan Alternatif dari Limbah Sayuran untuk Ikan Nila Hitam (Oreochromis niloticus) [ Alternative Feed from Vegetable Waste for Black Tilapia (Oreochromis niloticus)] - Abdul Manan; Aisya Maulyna Santoso (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Tilapia (Oreochromis sp) is the one commodity that very popular in the public. Besides low cost, good taste, protein content is also high. Feed is an element that is very supportive in an aquaculture operations. The main raw material in the artificial feed is fish meal and soy flour because it has a high protein content but is relatively expensive so it needs an alternative feed material. The purpose of this study is improve knowledge and skilled about feeding alternative production of vegetable waste and its effect on the growth of black tilapia. Study was conducted in Freshwater Aquaculture Management Unit which located in Kepanjen District, Malang Regency, Province of East Java started from January 20th until February 14th 2014. Work method which used was descriptive method by collecting primary data and secondary data. The data was collected by active participation, observation, interviewing, and study paper. The process of making feed alternative vegetable waste composed by several stage is preparation tools and materials, counting materials, production additives, blending, mixing, fermentation, and storage. The results of the evaluation of growth black tilapia feeding vegetable wastes little slow because of the low protein content